2021
DOI: 10.3390/ijerph18084186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Physical Training Programs on the Cognitive Status of a Group of Older Adults in Chile

Abstract: Introduction: The effect of two physical training methods on older adults should be investigated in greater depth and its results shared with the community. Objective: To determine the effects of two types of physical training on the functional features associated with the cognitive state and the effect on a physiological mediator of growth hormone (IGF-1) in older women. Material and Methods: Quasi-experimental study that included 12 weeks of training in two groups divided into resistance and aerobic training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have shown the effectiveness of muscle strength and power training [44][45][46][47]; however, precaution is also recommended in the evaluation of this population regarding the adaptation to the loads [48]. Similarly, many studies have reported improvements in the cognition level in people who carried out muscle strength training programmes [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the effectiveness of muscle strength and power training [44][45][46][47]; however, precaution is also recommended in the evaluation of this population regarding the adaptation to the loads [48]. Similarly, many studies have reported improvements in the cognition level in people who carried out muscle strength training programmes [49][50][51].…”
Section: Discussionmentioning
confidence: 99%